180k views
0 votes
What is the reason for each step in the solution of the equation?

−6x+7x+14=3

User Steabert
by
7.8k points

1 Answer

3 votes
-6x + 7x + 14 = 3
First, you add the variables x between each other so we can have one number with variable x:
x + 14 = 3
Then, subtract 14 from each side to get the variable x alone of a side, and its value on the other side:
x + 14 - 14 = 3 - 14
x = - 11

You can re-check your answer (very important):
-6x + 7x + 14 = -6(-11) + 7(-11) + 14 = 66 - 77 + 14 = -11 + 14 = 3
The answer has been approved.

Hope this Helps! :)
User Geirha
by
7.7k points